ANALISIS FUNGSIONALISASI HASIL BELAJAR WARGA BELAJAR KEAKSARAAN DI KECAMATAN SUKAMAKMUR KABUPATEN BOGOR - Elais Retnowati (Jurnal Ilmiah Visi, 2015)
The purpose of this research was to describe the real condition of functioning learning achievement of the literacy of the learning community members in Sukamakmur Sub-district, Bogor District. The research based on qualitative approach was conducted as from April through September 2013 in Sukaresmi village and Sukadamai village. The data were collected by observation, interview, and field note taking. The data were analyzed by structuring, clarifying. The findings show, the ability of learning community members in Functional Literacy program in Sukaresmi and Sukadamai just reach at the level of skills and basic competence. The research recommends to accelerate to independent literacy as the important basic to improve the quality of their life.